2015
DOI: 10.54386/jam.v17i1.979
|View full text |Cite
|
Sign up to set email alerts
|

Validation of InfoCrop model for rice cultivar under eastern plain zone of Uttar Pradesh

Abstract: The InfoCrop v 1.1 model was calibrated and validated with experimental data of 3 cultivars of rice (NDR-97, NDR-359 and Swarna Sub-1) conducted during 2002-2012 at Kumarganj, Faizabad (U.P.). The model performance was evaluated using MAE, MBE, RMSE and it was observed that InfoCrop model was able to predict the growth parameters like days taken to anthesis, maximum leaf area index, biomassand yield with reasonably good accuracy (error % less than 10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…The Bi 2 O 3 NPs have been tested to evaluate their effects on the healing of superficial wounds, but without infection, demonstrating accelerated wound healing (Dalvand et al, 2018;Hassan et al, 2023). It is also known that bimetallic nanoparticles have greater antimicrobial activity compared with the use of monometallic nanoparticles (Gulam Mohammed et al, 2014;Perdikaki et al, 2016;Kumar et al, 2019;Arora et al, 2020). Therefore, our formulation of metallic NPs is an ideal candidate to combat infection mainly in superficial wounds because it can eliminate the bacterial load of established infections and does not present toxicity on endothelial, epithelial, and fibroblast cells (Figure 9), which are necessary for angiogenesis and tissue regeneration (Wilkinson and Hardman, 2020), a crucial process for wound healing.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The Bi 2 O 3 NPs have been tested to evaluate their effects on the healing of superficial wounds, but without infection, demonstrating accelerated wound healing (Dalvand et al, 2018;Hassan et al, 2023). It is also known that bimetallic nanoparticles have greater antimicrobial activity compared with the use of monometallic nanoparticles (Gulam Mohammed et al, 2014;Perdikaki et al, 2016;Kumar et al, 2019;Arora et al, 2020). Therefore, our formulation of metallic NPs is an ideal candidate to combat infection mainly in superficial wounds because it can eliminate the bacterial load of established infections and does not present toxicity on endothelial, epithelial, and fibroblast cells (Figure 9), which are necessary for angiogenesis and tissue regeneration (Wilkinson and Hardman, 2020), a crucial process for wound healing.…”
Section: Figurementioning
confidence: 99%
“…Nonetheless, the combination does not have a synergic effect when administered independently (Iftikhar et al, 2021). In addition, some studies indicated that the use of bimetallic nanoparticles on infected wounds, such as gold and silver (Au-Ag NPs), speeds the healing process, making it more effective and safer, without adverse toxicity (Kumar et al, 2019). We propose that bismuth and silver bimetallic nanoparticles have a greater antimicrobial effect on S. aureus and E. coli when applied in lower doses than those reported as monometallic nanoparticles, having lower toxicity in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Chiraigaon block is one among the 8 blocks in Varanasi district which is located in the centre of the Gangetic plain of northern India, in the eastern part of the state of Uttar Pradesh, at an elevation of 80.71 metres form mean sea level [6]. From Chiraigaon block 54 representative surface soil samples were collected from cultivated field of six villages namely Umaraha, Khanpur, Bariyasanpur, Sivon, Paterwan and Sathwa.…”
Section: Experimental Sitementioning
confidence: 99%
“…A significant number of scholars investigated the viability of using recycled glass as a substitute for either fine or coarse aggregate. Other researchers took advantage of the pozzolanic qualities that glass powder possesses in order to partially replace cement in their research [10]. This was done by using the powder.…”
Section: Using Waste Glass In Concrete As An Ingredientmentioning
confidence: 99%